Bioethics on dialogue - Palazzani, Laura (Medicina e Morale, 2023)
Bioethics is dialogical as a 'bridge' between two cultures, scientific culture and humanistic culture and because of pluralism. The article analyzes the different theoretical ways to conceive dialogue in the liberal-libertarian perspective (as negotiation procedures), in the utilitarian vision (agreed calculation of convenience) and personalist view (recognition of the dignity of each human being). Bioethics Committees play a key role, both at national, regional and international levels, engaging in dialogue, considering both interdisciplinarity and pluralism in order to identify (if possible) an 'ethical mediation', which should not be reduced to a mere compromise or pragmatic agreement, but as a minimum level (or maximum possible level) of shared ethical principles/values on specific topics. Beyond the institutionalization of Bioethics with the Committees, the role of 'active citizenship' and 'citizen participation' is growing in importance in bioethics, along with the need to build platforms for dialogue with society (beyond experts), which enable dynamic updating and active interaction between experts and citizens.